A Case Study Evaluation of the Implementation of Twice-Exceptional Professional Development in Colorado. (December 2019) - Lee, Chin-Wen; Ritchotte, Jennifer A.
According to the 2014–2015 State of the States in Gifted Education, Colorado is the only state in the United States where a series of on-site, customized twice-exceptional professional development (2E PD) opportunities have been implemented. The purpose of this case study evaluation was to understand the implementation of 2E PD during 2014–2016 in a school district in Colorado. Seven training participants and four administrators who were involved in the training were purposefully selected. Data sources consisted of interviews, documentation, and archival records. Eight major themes emerged: (a) increased knowledge and skills, (b) evolved attitudes, (c) recurring challenges, (d) utilizing a team approach, (e) improved performance, (f) difficulty in measuring impact, (g) improved school culture, and (h) planning for the future. In addition to a discussion of themes, implications for improving educator and student outcomes and for creating organizational support and changes are presented.